Relative Abundance of Wildlife Species using Camera Trap in SPTN I Long Bawan Kayan Mentarang National Park - Nugroho Sigit Darmawan; Ashari Wicaksono; M. Idham Aliem (Universitas Andi Djemma Palopo, 2024)
Kayan Mentarang National Park is the largest nature conservation area on the island of Kalimantan. In supporting activities to protect and preserve wild animals, it is necessary to know their numbers and distribution. Observing wild animals often faces challenges because the characteristics of the animals themselves are shy, cryptic and elusive. It makes them difficult to find directly. Especially in TNKM, this condition is exacerbated by the topography and area size. This research aims to determine species richness, species diversity, encounter rates, abundance and activity patterns of wild animals using camera traps at SPTN I Long Bawan TNKM. The research results found 31 types of wild animals belonging to 17 families. The wild animal encounter rate value was dominated by Macaca nemestrina (ER 2,984 photos/day). The Diversity Index (H') value is classified as moderate with a value of 2.19. The wild animal that has the highest species abundance value is Macaca nemestrina (RAI 18.96%). The daily activity patterns of wild animals are classified as active at night (nocturnal) with as many as 8 species (26%), active during the day (diurnal) with as many as 14 species (45%) and active at both times (nocturnal and diurnal) as many as 9 species (29%).